Hepatotoxicity Induced by Herbal and Dietary Supplements - Navarro, Victor J.; Lucena, M. Isabel (Seminars in Liver Disease, 2014)
Herbals and dietary supplements (HDS) can cause hepatotoxicity. Regulation of HDS varies across the globe. In the United States, it is defined by a law that is now two decades old. More recent regulatory approaches in Europe still do not require testing for premarket safety. The true incidence of hepatotoxicity from HDS is unknown. The presentation is most often with a hepatocellular enzyme pattern, and the outcomes can be severe, leading to transplantation in some circumstances. The diagnosis of hepatotoxicity due to HDS is made in the same way as for drugs. However, patients often must be coaxed into revealing a history of use. No causality assessment approach is perfectly suited for hepatotoxicity from HDS, but the Roussel Uclaf Causality Assessment Method is most used. Future endeavors must focus on defining epidemiology, establishing an accepted nomenclature, and identifying culprit ingredients, predisposing host factors, and useful biomarkers for injury.
Keywords: herbal and dietary supplements; hepatotoxicity; drug-induced liver injury